Nursing workloads and activity in critical care: A review of the evidence. (October 2018) - Greaves, Jane; Goodall, Deborah; Berry, Andrea; Shrestha, Suman; Richardson, Annette; Pearson, Pauline
Abstract: Objectives: To review current methods for informing nurse workforce decisions in critical care. Many clinical outcomes are worse if staffing is inadequate. Workforce planning is usually according to guidelines developed from the opinions of expert groups. Objective systems for planning and distributing staff have been developed but their value is unclear. Design: A rapid review methodology was employed. Review methods: The search included research studies, guidelines and surveys within and outside United Kingdom since 1995. Findings: Thirty-two studies met eligibility criteria. Studies originated worldwide, with considerable work undertaken in the United Kingdom and Brazil. Two were large multicentre studies. Tools examined fell into three groups: those focused on the condition and needs of the patient, those focused on the number and time for nursing activities and those that also took account of psycho-social factors. Many tools were not used beyond their country of origin. Conclusion: There is limited experience of using tools to determine nurse staffing. No one tool is likely to suit every application. More information is needed to clarify the practicalities of using the tools.